Messverfahren für die akustische Absorption zur Bestimmung der Volumenviskosität - Claes, Leander

Schlieren imaging with fractional Fourier transform to visualise ultrasonic fields - Hetkämper, Tim; Claes, Leander; Henning, Bernd (Sensoren und Messsysteme - Beiträge der 21. ITG/GMA-Fachtagung)

Identification of piezoelectric material parameters using optimised multi-electrode specimens - Claes, Leander; Feldmann, Nadine; Schulze, Veronika; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

Differentiation of an SBFE model in the context of material parameter determination - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Birk, Carolin; Henning, Bernd

Estimation of piezoelectric material parameters of ring-shaped specimens - Friesen, Olga; Claes, Leander; Feldmann, Nadine; Henning, Bernd

Lamb wave based approach to the determination of acoustic material parameters - Johannesmann, Sarah; Claes, Leander; Feldmann, Nadine; Zeipert, Henning; Henning, Bernd (tm - Technisches Messen)
Abstract In this paper a measurement procedure to identify viscoelastic material parameters of plate-like samples using broadband ultrasonic waves is presented. Ultrasonic Lamb waves are excited via the thermoelastic effect using laser radiation and detected by a piezoelectric transducer. The resulting measurement data is transformed to yield information about multiple propagating Lamb waves as well as their attenuation. These results are compared to simulation results in an inverse procedure to identify the parameters of an elastic and a viscoelastic material model.
Keywords: Electrical and Electronic Engineering; Instrumentation

Estimation of viscoelastic material parameters of polymers using Lamb waves - Johannesmann, Sarah; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

Inverses Verfahren zur Bestimmung viskoelastischer Materialparameter - Johannesmann, Sarah

Quantifying the coupling strength of adhesively bonded materials by investigating mode repulsion regions - Zeipert, Henning; Johannesmann, Sarah; Nicolai, Marcel; Lugovtsova, Yevgeniya; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)